2014
DOI: 10.1021/nn500085k
|View full text |Cite
|
Sign up to set email alerts
|

Versatile RNA Interference Nanoplatform for Systemic Delivery of RNAs

Abstract: Development of nontoxic, tumor-targetable, and potent in vivo RNA delivery systems remains an arduous challenge for clinical application of RNAi therapeutics. Herein, we report a versatile RNAi nanoplatform based on tumor-targeted and pH-responsive nanoformulas (NFs). The NF was engineered by combination of an artificial RNA receptor, Zn(II)-DPA, with a tumor-targetable and drug-loadable hyaluronic acid nanoparticle, which was further modified with a calcium phosphate (CaP) coating by in situ mineralization. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 36 publications
(77 reference statements)
3
82
0
Order By: Relevance
“…The lower tumor:liver ratio observed with in vivo jetPEI and nanoparticle systems in the literature is consistent with reported challenges in achieving efficient nanoparticle delivery to tumor sites; in a comprehensive analysis of nanoparticle delivery to solid tumors, the median injected dose delivered to the tumor site was 0.7% (47). It is notable that even in recent, advanced, and promising nanoparticle systems, including those that use modifications for "stealth" or targeting mechanisms, the ratio of tumor:liver accumulation is consistently close to or below 1:1 (3,5,(57)(58)(59)(60)(61)(62). The marked improvement of siRNA-L 2 in relative tumor accumulation supports its translational promise.…”
Section: Discussionsupporting
confidence: 77%
“…The lower tumor:liver ratio observed with in vivo jetPEI and nanoparticle systems in the literature is consistent with reported challenges in achieving efficient nanoparticle delivery to tumor sites; in a comprehensive analysis of nanoparticle delivery to solid tumors, the median injected dose delivered to the tumor site was 0.7% (47). It is notable that even in recent, advanced, and promising nanoparticle systems, including those that use modifications for "stealth" or targeting mechanisms, the ratio of tumor:liver accumulation is consistently close to or below 1:1 (3,5,(57)(58)(59)(60)(61)(62). The marked improvement of siRNA-L 2 in relative tumor accumulation supports its translational promise.…”
Section: Discussionsupporting
confidence: 77%
“…There is a critical need to develop drug delivery platforms in order to expedite the clinical translation of miRNA based therapeutics. 19 26 Delivery approaches employed thus far for gene delivery range from viral platforms 27 to nonviral carriers based on polymer, 28 lipid, 29 and dendrimeric 30 backbones. Although viral platforms have been shown to provide potent gene knockdown, viral construct mediated gene silencing has been hindered in the clinical setting due to toxic immune responses and potential integration into the host genome, leading to the widespread development of nonviral carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Here we describe a highly flexible protocol to design a sophisticated RNA carrier that we used for tumor-targeted RNA delivery in our previous studies, which is distinct from the reported gene delivery systems that are based on cationic derivatives or chemically modified RNAs 10,11 . This is an alternative RNA delivery system based on the use of Zn-DPA analog, an artificial receptor for phosphate anion derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Similar Zn-DPA analogs were also used as probes for necrotic and apoptotic cells by targeting anionic phosphatidylserine on cell surfaces 16,17 . Recently, we applied Zn-DPA analogs as carriers for the delivery of therapeutic molecules, such as siRNA, using the selective and strong binding of Zn-DPA with the phosphodiester groups on the siRNA back-bone 10,11 . In particular, this Zn-DPA platform for RNA delivery is highly flexible and can be used in conjunction with existing delivery systems such as NPs, polymers, proteins and antibodies by simply labeling the small-molecule Zn-DPA by established bioconjugation chemistry.…”
Section: Introductionmentioning
confidence: 99%